Lon, a Stress-Induced ATP-Dependent Protease, Is Critically Important for Systemic Salmonella enterica Serovar Typhimurium Infection of Mice - Takaya, Akiko (American Society for Microbiology, 2003)
Studies on the pathogenesis of Salmonella enterica serovar Typhimurium infections in mice have revealed the presence of two prominent virulence characteristics—the invasion of the nonphagocytic cells to penetrate the intestinal epithelium and the proliferation within host phagocytic cells to cause a systemic spread and the colonization of host organs. We have recently demonstrated that the ATP-dependent Lon protease of S. enterica serovar Typhimurium negatively regulates the efficiency of invasion of epithelial cells and the expression of invasion genes (A. Takaya et al., J. Bacteriol. 184:224-232, 2002). This study was performed to reveal the contribution of the Lon protease to the virulence of S. enterica serovar Typhimurium in mice. Determination of 50% lethal doses for the lon disruption mutant and wild-type strain revealed that the mutant was highly attenuated when administered either orally or intraperitoneally to BALB/c mice. The mutant was also found to be able to reach extraintestinal sites but unable to proliferate efficiently within the spleen and cause lethal systemic disease of mice. Macrophage survival assays revealed that the lon disruption mutant could not survive or proliferate within murine macrophages. In addition, the mutant showed extremely increased susceptibility to hydrogen peroxide, which contributes to the bactericidal capacity of phagocytes. The mutant also showed increased sensitivity to acidic conditions. Taken together, the impaired ability of the lon disruption mutant to survive and grow in macrophages could be due to the enhanced susceptibility to the oxygen-dependent killing mechanism associated with respiratory burst and the low phagosomal pH. These results suggest that the Lon protease is essentially involved in the systemic infection of mice with S. enterica serovar Typhimurium, which can be fatal. Of further interest is the finding that the lon disruption mutant persists in the BALB/c mice for long periods without causing an overwhelming systemic infection.